If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2b+7)=-39
We move all terms to the left:
-3(2b+7)-(-39)=0
We add all the numbers together, and all the variables
-3(2b+7)+39=0
We multiply parentheses
-6b-21+39=0
We add all the numbers together, and all the variables
-6b+18=0
We move all terms containing b to the left, all other terms to the right
-6b=-18
b=-18/-6
b=+3
| 2(g-4)=8 | | 5(x+3)+6=3(x-1)-x | | 2x/3+x/5=4 | | 8x+6+7=-2+3x | | d²+1=2d | | -11y=55 | | -24=(5-2b)8 | | -2(3+x)=25 | | 3(x-3)+5=11 | | 4x+5(7x-3)=9x-45 | | 127=3(1+5m)+4 | | -10d+7=-9d | | 50-5x^2=-15x | | -2(-5x+5)-3x+4=−34 | | (3-2b)6=54 | | 2(y=9)-3(4y+2)=-8 | | 4m+3=-13-m | | 10+7b=5b | | -4+8n=4n-8+3n | | 10x-4=10x+6 | | x/1.5+3.75=8.25 | | 8+xx4=52 | | 4n-3n+6=6 | | 5-3(x+4)=7+2(x-1) | | 20=-10s | | (4x+10)+(2x-1)=9x-15 | | 8(2p-4)=32 | | 24(b+50)=3000 | | 5+5k=4k-3 | | 3(8x-5)=25x | | -9(2b+4)=90 | | 20x-2+12+6=90 |